Assessment of relationship between galectin-3 and ambulatory ECG-based microvolt T-wave alternans in sustained systolic-diastolic hypertension patients. Issue 5 (October 2016) - Pusuroglu, Hamdi; Akgul, Ozgur; Erturk, Mehmet; Bolat, Ismail; Tasbulak, Omer; Ornek, Vesile; Gul, Mehmet; Ozyilmaz, Sinem O.; Yildirim, Hayriye A.; Kokturk, Uğur; Yilmaz, Emre; Kalkan, Ali K.; et al.
Abstract : Objectives: Galectin-3 is a marker associated with myocardial fibrosis and left ventricular myocardial index (LVMI). Myocardial fibrosis and LVMI have been reported in many studies to be associated with microvolt T-wave alternans (MTWA) positivity. In this study, galectin-3 levels of normotensive individuals and sustained systolic-diastolic hypertensive patients were compared and the association between galectin-3 levels and ambulatory ECG-based MTWA was investigated. Methods: A total of 184 individuals were included in the study, among whom, 43 were normotensive and 141 had sustained systolic-diastolic hypertension without cardiovascular or chronic renal failure. Galectin-3, MTWA, and LVMI were evaluated in all participants. Galectin-3 levels of hypertensive and normotensive participants were compared. The association between galectin-3, MTWA, LVMI, and estimated glomerular filtration rate (eGFR) was investigated in hypertensive patients. Results: LVMI and galectin-3 levels were higher among hypertensive patients compared with normotensives (94.9±26.8 vs. 76.4±22.9 g/m 2, 7.325±2.123 vs. 5.233±1.506 ng/ml; P <0.001, P <0.001). Correlation analysis carried out among the hypertensive patients showed that the galectin-3 level was correlated positively to LVMI, age, and MTWA positivity ( r =0.396, P <0.001; r =0.358, P <0.001; r =0.361, P <0.001, respectively), whereas it was correlated negatively to eGFR and male sex ( r =−0.364, P <0.001; r =−0.280, P =0.001, respectively). Multiple logistic regression analysis indicated that LVMI and galectin-3 showed an independent association with MTWA positivity in hypertensive patients ( P =0.003 and 0.005, respectively). Conclusion: Increased galectin-3 levels are associated with ambulatory ECG-based MTWA positivity, decreased eGFR, and increased LVMI in hypertensive patients. This association may be used for risk classification in this patient group.